Textured tantalum-plated carbon nanotube-containing PVA titanium mesh titanium-based bionic joint material and preparation method thereof
By textured treatment and tantalum plating on the surface of the titanium alloy, and adding carbon nanotubes to the PVA hydrogel, forming a carbon nanotube-containing PVA-titanium mesh composite hydrogel material, the hydrogel in the human environment is solved The issues of service reliability and service life significantly improve the strength, toughness and corrosion resistance of the material.
Patent Information
- Application Number
- CN202411460549.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-25
AI Technical Summary
The reliability and service life of existing hydrogel-titanium alloy composites in human environments are restricted by insufficient strength and toughness of the hydrogel itself, reduced mechanical properties resulting from swelling, and corrosion problems.
By textured treatment, magnetron sputtering tantalum plating, hydroxylation and silanization treatment on the surface of the titanium alloy, and carbon nanotubes are added to the PVA hydrogel to form a carbon nanotube-containing PVA-titanium mesh composite hydrogel Material, strengthening the strength and toughness of the material.
It significantly improves the strength and toughness of the hydrogel, alleviates the decline in mechanical properties caused by swelling, enhances the corrosion resistance of the material, and improves the bonding strength and stability of the hydrogel and titanium alloy matrix.
Smart Images

Figure CN119506799A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterials, and specifically relates to a textured tantalum-plated carbon nanotube-containing PVA titanium mesh titanium-based bionic joint material and a preparation method thereof. Background Art
[0002] After being damaged, human articular cartilage tissue is difficult to repair itself and must be repaired or replaced with materials that can replace the natural articular cartilage structure. However, after extensive exploration by researchers, no material that matches the structural properties of human natural articular cartilage has been found. Natural articular cartilage has special lubrication properties and good load-bearing capacity, which is based on the lubricating biomacromolecules on its permeable surface and the hierarchical structure of gradient orientation. Hydrogel has excellent flexibility, good biocompatibility and low friction coefficient, and is considered to be the most promising cartilage replacement material. The soft-hard composite multilayer material composed of hydrogel and titanium alloy substrate is superior to the traditional single hydrogel material, has good biocompatibility and high load-bearing capacity, and excellent low friction coefficient, and has received attention in the field of joint repair.
[0003] The volume expansion, mechanical property degradation, and interface bonding degradation caused by the swelling of hydrogels in body fluids restrict the strong adhesion of hydrogels, which is the root cause of reduced service time and interface debonding failure. In order to ensure the reliability and service life of hydrogel-titanium alloy composite materials in the human body environment, this patent proposes a method for preparing a PVA-titanium mesh composite hydrogel bionic joint multilayer structure with strong adhesion on the textured titanium alloy tantalum-plated surface.
[0004] Titanium alloy surface texturing is a technology that improves the performance of titanium alloys by changing the microstructure of the titanium alloy surface. Among them, laser micromachining is an effective texturing method, which can prepare microtextures with different morphologies and distribution densities on the titanium alloy surface. Through laser micromachining, the size and shape of the texture can be precisely controlled to achieve the optimal texture parameters. The tribological properties and biocompatibility of titanium alloy surfaces under different texture parameters can be significantly improved. When hydrogel is filled into its micropores, the formed interface micro-nano hierarchical structure can provide a larger surface area and more mechanical locking points due to its multi-scale effect, increase the interface area, increase the interface crack propagation path by several orders of magnitude, and greatly increase the interface energy consumption. It is an effective method to significantly improve the toughness and bonding strength of the hydrogel-titanium alloy interface. Tantalum metal has a wide range of applications in the medical field, mainly due to its excellent corrosion resistance and biocompatibility. Plating tantalum on the surface of titanium alloy can effectively improve the corrosion resistance and biocompatibility of the titanium alloy surface, thereby achieving the purpose of surface modification of titanium alloy. Hydroxylation of titanium alloy surface is a method to treat the titanium alloy surface into a form with hydroxyl groups in order to increase surface adhesion, corrosion resistance and wear resistance. After hydroxylation, silane molecules are adsorbed on the titanium surface through silanization to form hydrogen bonds with the hydroxyl groups on the titanium surface, and cross-link into a spatial network structure through mutual hydrogen bonding. This modification can form a protective film on the titanium alloy surface, improving its corrosion resistance and wear resistance.
[0005] Patent CN202311339416.1 discloses a textured titanium alloy tantalum-plated PVA-titanium mesh hydrogel bionic joint and a preparation method. This method adds a titanium mesh to the traditional hydrogel-titanium alloy composite material and performs tantalum plating on the surface of the titanium alloy, thereby improving the bonding strength of the composite material. However, this method does not improve the strength of the hydrogel itself. Hydrogels absorb water in the body, and swelling commonly causes a decrease in strength and toughness, and corrosion occurs over time. Therefore, there is an urgent need for a hydrogel enhancement and modification method to improve the strength and toughness of the hydrogel itself, and to improve corrosion resistance to prevent local fracture and corrosion of the hydrogel. Summary of the invention
[0006] The purpose of the present invention is to provide a textured tantalum-plated carbon nanotube-containing PVA titanium mesh titanium-based bionic joint material and a preparation method thereof.
[0007] The technical solution to achieve the purpose of the present invention is: a method for preparing a textured tantalum-plated carbon nanotube-containing PVA titanium mesh titanium-based bionic joint material, comprising the following steps:
[0008] Step (1): surface treatment of titanium alloy;
[0009] Step (2): texturing the titanium alloy surface using a femtosecond laser;
[0010] Step (3): plating tantalum on the surface of the textured titanium alloy by magnetron sputtering in an argon atmosphere;
[0011] Step (4): cleaning and drying;
[0012] Step (5): hydroxylation treatment;
[0013] Step (6): silanization treatment;
[0014] Step (7): preparing a PVA solution containing carbon nanotubes;
[0015] Step (8): placing the titanium alloy after silanization treatment in step (6) into a mold, pouring the PVA solution prepared in step (7), and placing the titanium alloy mesh; then pouring the PVA solution prepared in step (7), drying, and demolding to obtain a semi-finished bionic joint material;
[0016] Step (9): Annealing the semi-finished bionic joint material obtained in step (8) to obtain a titanium-based bionic joint material.
[0017] Furthermore, the surface treatment in step (1) is specifically: grinding and polishing the surface of the titanium alloy using sandpaper.
[0018] Furthermore, step (2) is specifically as follows: the circular dimple texture obtained by texturing treatment in step (2) has a diameter of 50-200 μm, a depth of 95-105 μm, and a texturing density of 10%-40%.
[0019] Furthermore, in step (3), the target-substrate distance of magnetron sputtering is 80 mm, the incident angle is 65°, and the back-bottom vacuum is less than 5.0×10 -3 Pa, working gas pressure 0.8-0.9Pa, argon flow rate 50sccm, magnetron sputtering power 100-120W, sputtering time 90-100min.
[0020] Furthermore, step (4) is specifically as follows: ultrasonically clean the product in acetone for 20-30 minutes, ultrasonically clean the product in anhydrous ethanol and deionized water for 10-20 minutes, and dry the product in a vacuum drying oven.
[0021] Further, step (5) is specifically: placing in 60±1°C, 5 mol / L NaOH solution for hydroxylation treatment;
[0022] Step (6) is specifically as follows: rinse the hydroxylated titanium alloy with deionized water, repeatedly rinse until the pH of the leaching solution is 7; place it under natural conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of deionized water, anhydrous ethanol and acetone, and then heat it in a constant temperature water bath at 80±2°C for 8±1h, while stirring at a uniform speed and adding 8mL of silane coupling agent KH-570 dropwise to complete the silanization treatment.
[0023] Furthermore, step (7) is specifically as follows: weighing carbon nanotubes, acid washing, adding deionized water and stirring in a constant temperature water bath at 90±2° C. until completely dissolved to obtain a carbon nanotube solution;
[0024] Weigh PVA solid and dissolve it in the carbon nanotube solution, then add deionized water and slowly stir it in a constant temperature water bath at 90±2°C for 5±0.5h; then raise the temperature to 95±2°C, let it stand for 1±0.1h, and remove bubbles; the degree of polymerization of the obtained PVA solution is 1750±50.
[0025] Furthermore, step (8) is specifically as follows: placing the titanium alloy in a mold, pouring 10-12 mL of the PVA solution containing carbon nanotubes into the mold, implanting a titanium alloy mesh with a thickness of 0.04-0.06 mm, letting it stand for 60±10 s, pouring another 10-12 mL, letting it stand for 60±10 s, and finally placing it in a drying oven and drying it at 35±2°C for 48±5 h.
[0026] Furthermore, the annealing in step (9) is specifically: annealing at 100±5°C for 3±0.1h.
[0027] A textured tantalum-plated carbon nanotube-containing PVA titanium mesh titanium-based bionic joint material is prepared by the above method.
[0028] Compared with the prior art, the present invention has the following significant advantages:
[0029] (1) Adding carbon nanotubes to PVA hydrogel, carbon nanotube hydrogel has excellent mechanical properties, and its elastic modulus and tensile strength are much higher than traditional gel materials. The huge internal volume of the hydrogel provides a large number of binding sites for the surface functions of the carbon nanotubes. The treatment method introduced in this patent makes the carbon nanotubes evenly dispersed in the hydrogel matrix. Studies have found that carbon nanotubes interact with the hydrogel matrix, and their surfaces carry a large number of functional hydrophilic groups such as carboxyl, hydroxyl, and amino groups. On the one hand, they can increase the dispersion concentration and uniformity of carbon nanotubes in aqueous solution, and on the other hand, they can enhance their interaction with polymers in the hydrogel matrix, thereby significantly improving the mechanical properties of carbon nanotube-based hydrogels. The new composite material structure formed improves the strength and toughness of the hydrogel, and alleviates the adverse phenomenon of decreased mechanical properties caused by the swelling of the hydrogel.
[0030] (2) Tantalum is plated on the surface by magnetron sputtering, and then hydroxylation and silanization are performed to form tantalum hydroxide, which has certain biological activity. At the same time, due to the introduction of hydroxyl groups, hydrogen bonds are further formed, thereby improving the bonding strength between the hydrogel and the titanium alloy matrix. In the simulated body fluid environment test, the bonding performance of the material of the present invention under swelling conditions also shows a certain stability.
[0031] (3) The titanium alloy mesh was inserted into the PVA hydrogel, which effectively improved the strength of the hydrogel and enabled the composite material to exist stably under swelling conditions. At the same time, it solved the problem of PVA hydrogel being insufficient in strength and easy to break. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the preparation method of the present invention.
[0033] Figure 2 Peeling curve of PVA-titanium mesh composite hydrogel containing carbon nanotubes on textured titanium alloy plated with tantalum.
[0034] Figure 3 Comparison of the bonding strength of the PVA-titanium mesh composite hydrogel of textured titanium alloy and the bonding strength of the carbon nanotube mesh composite hydrogel of textured titanium alloy under swelling conditions.
[0035] Figure 4 Comparison of the fracture strength of PVA-titanium mesh composite hydrogel and carbon nanotube mesh composite hydrogel under swelling conditions.
[0036] Figure 5 Actual photo of carbon nanotube-containing PVA-titanium mesh composite hydrogel on the textured tantalum-plated titanium alloy surface.
[0037] Figure 6 Actual picture of the layered structure of carbon nanotube-containing PVA-titanium mesh composite hydrogel on the textured tantalum-plated titanium alloy surface. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0039] The purpose of the present invention is to solve the problem of poor bonding of existing bionic articular cartilage multilayer materials, and to provide a technical means for preparing titanium alloy / hydrogel bionic articular cartilage with strong and tough adhesion. On the one hand, the surface is magnetron sputtered and tantalum is plated on the basis of composite modification (texturing and hydroxylation silanization) of the titanium alloy surface. The presence of the tantalum layer not only improves the biological activity but also enhances the stability of the interface bonding under swelling conditions. On the other hand, the titanium alloy mesh is implanted in the PVA hydrogel to improve the strength of the hydrogel and further enhance the comprehensive performance of the composite material. This method for preparing a carbon nanotube-containing PVA-titanium mesh composite hydrogel bionic joint multilayer structure with strong and tough adhesion on the textured titanium alloy tantalum-plated surface will solve the difficulties of the prior art and improve the strength and stability of articular cartilage materials.
[0040] Combination Figure 1 The artificial articular cartilage of the present invention is composed of a lubricating layer and a substrate, and its preparation method includes the following steps: The technical solution to realize the present invention is: a textured titanium alloy tantalum-plated surface with strong and tough adhesion to the carbon nanotube PVA-titanium mesh composite hydrogel bionic joint multilayer structure, the artificial articular cartilage is prepared by casting and drying the lubricating layer and the substrate, the substrate is a titanium alloy with surface texturing and then magnetron sputtering tantalum plating, and the lubricating layer is a physically cross-linked carbon nanotube PVA hydrogel implanted in the titanium alloy mesh.
[0041] Example 1
[0042] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0043] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 200μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 10% is obtained;
[0044] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3 Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0045] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0046] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0047] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0048] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0049] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0050] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 48 h.
[0051] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0052] Example 2
[0053] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0054] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 200μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 20% is obtained;
[0055] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3 Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0056] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0057] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0058] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0059] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0060] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0061] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 48 h.
[0062] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0063] Example 3
[0064] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0065] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 200μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 30% is obtained;
[0066] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3 Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0067] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0068] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0069] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0070] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0071] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0072] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 48 h.
[0073] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0074] Example 4
[0075] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0076] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 200μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 40% is obtained;
[0077] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0078] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0079] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0080] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0081] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0082] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0083] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 48 h.
[0084] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0085] Example 5
[0086] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0087] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 150μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 20% is obtained;
[0088] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3 Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0089] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0090] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0091] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0092] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0093] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0094] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 48 h.
[0095] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0096] Example 6
[0097] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0098] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 100μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 20% is obtained;
[0099] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3 Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0100] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0101] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0102] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0103] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0104] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0105] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 48 h.
[0106] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0107] Example 7
[0108] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0109] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 200μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 10% is obtained;
[0110] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0111] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0112] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0113] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0114] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0115] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0116] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 60 h.
[0117] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0118] Example 8
[0119] (1) Use 80 mesh, 180 mesh, 400 mesh and 800 mesh sandpaper to grind the surface of titanium alloy flat.
[0120] (2) Using femtosecond laser pulses to texture a circular micropore array on the surface of Ti6Al4V (25mm×25mm×6mm, Ra=~0.02μm) obtained in (1). The method uses a laser spot with a wavelength of 1064nm, a diameter of 1.0μm, a power of about 20W, and an energy of about 350mJ to ablate the circular micropore texture. A circular micropore texture with a diameter of 200μm and a depth of about 100μm is obtained. By controlling the distance between the centers of the micropores, a density of 10% is obtained;
[0121] (3) Using DC magnetron sputtering method, in argon atmosphere, use A high-purity tantalum target is sputtered on the surface of the textured titanium alloy obtained in (2) to obtain a tantalum layer. The process parameters of DC magnetron sputtering are: target-substrate distance 80 mm, incident angle 65°, sputtering chamber vacuum degree less than 5.0×10 -3 Pa, the working gas pressure is 0.8Pa, the argon gas flow rate is 50sccm, the sputtering power is 100W, and the sputtering time is controlled to be 90min;
[0122] (4) The textured titanium alloy after surface magnetron sputtering tantalum plating was first placed in acetone for ultrasonic cleaning for 20 minutes, then placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes, and then dried;
[0123] (5) Weigh 40 g of NaOH and dissolve it in 200 mL of deionized water, stirring evenly. Place the textured titanium alloy with tantalum on the surface in (3) in the above NaOH solution and keep it in a constant temperature water bath at 60° C. for 24 h for hydroxylation;
[0124] (6) Rinse the titanium alloy that has been hydroxylated in (5) with deionized water, and rinse repeatedly until the pH of the leaching solution is 7. Place it under natural drying conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of 40 mL deionized water, 360 mL anhydrous ethanol, and 10 mL acetone, and then heat it in a constant temperature water bath at 80°C for 8 h, while stirring slowly and uniformly, and add 8 mL of silane coupling agent (KH-570) dropwise;
[0125] (7) Weigh 0.8g of carbon nanotubes, pickle in a small amount of sulfuric acid solution for 3h, add 200mL of deionized water and stir in a 90℃ constant temperature water bath until completely dissolved. Weigh 82g of PVA and dissolve it in the carbon nanotube solution, then add 300mL of deionized water and stir slowly in a 90℃ constant temperature water bath for 5h. Then heat to 95℃, let stand for 1h to remove bubbles;
[0126] (8) taking out the hydroxylated silanized tantalum-titanium alloy, repeatedly rinsing it with anhydrous ethanol and deionized water, and blowing the surface dry;
[0127] (9) The titanium alloy treated in (8) was placed in a mold, 10 mL of the carbon nanotube-containing PVA solution obtained in (7) was pre-poured into the mold, a titanium alloy mesh (85 mm*25 mm*0.05 mm) was implanted, and the mixture was allowed to stand for 60 s. Then, 10 mL of the mixture was poured again, and the mixture was allowed to stand for 60 s. Finally, the mixture was placed in a drying oven and dried at 35 °C for 72 h.
[0128] (10) Take out the composite material dried in (9), demold it, and anneal it at 100° C. for 3 h.
[0129] Comparative example: Textured unplated tantalum-titanium alloy PVA hydrogel composite material.
Claims
1. A method for preparing a textured tantalum-plated carbon nanotube-containing PVA titanium mesh titanium-based bionic joint material, characterized in that: The steps include: Step (1): surface treatment of titanium alloy; Step (2): texturing the titanium alloy surface using a femtosecond laser; Step (3): plating tantalum on the surface of the textured titanium alloy by magnetron sputtering in an argon atmosphere; Step (4): cleaning and drying; Step (5): hydroxylation treatment; Step (6): silanization treatment; Step (7): preparing a PVA solution containing carbon nanotubes; Step (8): placing the titanium alloy after silanization treatment in step (6) into a mold, pouring the PVA solution prepared in step (7), and placing the titanium alloy mesh; then pouring the PVA solution prepared in step (7), drying, and demolding to obtain a semi-finished bionic joint material; Step (9): Annealing the semi-finished bionic joint material obtained in step (8) to obtain a titanium-based bionic joint material.
2. The method according to claim 1, characterized in that The surface treatment in step (1) is specifically: grinding and polishing the surface of the titanium alloy using sandpaper.
3. The method according to claim 1, characterized in that Step (2) is specifically as follows: the circular dimple texture obtained by texturing treatment in step (2) has a diameter of 50-200 μm, a depth of 95-105 μm, and a texturing density of 10%-40%.
4. The method according to claim 1, characterized in that: In step (3), the target-substrate distance of magnetron sputtering is 80 mm, the incident angle is 65°, and the back vacuum is less than 5.0×10 -3 Pa, working gas pressure 0.8-0.9Pa, argon flow rate 50sccm, magnetron sputtering power 100-120W, sputtering time 90-100min.
5. The method according to claim 1, characterized in that Step (4) is specifically as follows: ultrasonically clean the product in acetone for 20-30 min, ultrasonically clean the product in anhydrous ethanol and deionized water for 10-20 min, and dry the product in a vacuum drying oven.
6. The method according to claim 1, characterized in that Step (5) is specifically as follows: placing in a 60±1°C, 5 mol / L NaOH solution for hydroxylation treatment; Step (6) is specifically as follows: rinse the hydroxylated titanium alloy with deionized water, repeatedly rinse until the pH of the leaching solution is 7; place it under natural conditions, and after the surface of the titanium alloy is completely dry, place it in a mixed solution of deionized water, anhydrous ethanol and acetone, and then heat it in a constant temperature water bath at 80±2°C for 8±1h, while stirring at a uniform speed and adding 8mL of silane coupling agent KH-570 dropwise to complete the silanization treatment.
7. The method according to claim 6, characterized in that Step (7) specifically comprises: weighing carbon nanotubes, washing with acid, adding deionized water, and stirring in a constant temperature water bath at 90±2° C. until completely dissolved, to obtain a carbon nanotube solution; Weigh PVA solid and dissolve it in the carbon nanotube solution, then add deionized water and slowly stir it in a constant temperature water bath at 90±2°C for 5±0.5h; then raise the temperature to 95±2°C, let it stand for 1±0.1h, and remove bubbles; the degree of polymerization of the obtained PVA solution is 1750±50.
8. The method according to claim 7, characterized in that Step (8) is specifically as follows: placing the titanium alloy in a mold, pouring 10-12 mL of the PVA solution containing carbon nanotubes into the mold, implanting a titanium alloy mesh with a thickness of 0.04-0.06 mm, letting it stand for 60±10 s, pouring another 10-12 mL, letting it stand for 60±10 s, and finally placing it in a drying oven and drying it at 35±2°C for 48±5 h.
9. The method according to claim 8, characterized in that The annealing in step (9) is specifically: annealing at 100±5°C for 3±0.1h.
10. A textured tantalum-plated carbon nanotube-containing PVA titanium mesh titanium-based bionic joint material, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Multi-component super-molecular hydrogel and preparation method thereof
CN103242656A
Artificial caput femoris
CN105287057A
Textured titanium alloy tantalum-plated adhesion PVA-titanium mesh hydrogel bionic joint and preparation method thereof
CN117379593A